Experience performing partial fistulectomy through a single incision to treat pyriform sinus fistula in children. (December 2021) - Han, Liling; Zhao, Zhenzhen; Zhang, Jun; Kong, XiangRu; Yang, Chao; Peng, Liang; Lv, Lin Ya; Li, ChangChun; Wang, Shan; Wei, Guang Hui
Abstract: Background and objectives: The surgical treatment of pyriform sinus fistula (PSF) is improving. The aim of this study was to investigate the effect of partial fistula excision in children with PSF assisted by using methylene blue. Methods: According to the method used to treat PSF infection, the patients were divided into a conservative treatment group, a single incision group (the children drained the abscess through the incision at the dermatoglyph of the cricothyroid joint), and a non single incision group (the children drained the abscess through the incision in the most obvious area of the abscess or ulceration). The data were retrieved from the electronic medical records (EMRs) and hospital information system （HIS）. The patient and observer scar assessment scale (POSAS) scores at 6 months after fistula resection were compared. Results: A total of 239 patients diagnosed with PSF underwent partial resection of the fistula through cervical approach with methylene blue. The success rate of the operation was 100%. The average operation time was 32 ± 13.2 min. The average hospital stay was 1 ± 0.2 days. There were 2 cases of transient hoarseness and 6 cases of wound infection. There were 17 patients in the conservative treatment group, 81 patients in the single incision group and 145 patients in the nonsingle incision group. The average POSAS scores of the three groups were 2.56 ± 0.6, 3.12 ± 0.84 and 4.56 ± 1.56, respectively, with significant differences among the three groups ( P  < 0.05). Conclusions: Partial fistulectomy assisted by using methylene blue through a single incision in the neck for the treatment of PSF in children yields a high success rate, fewer postoperative complications and greater comfort than traditional surgery. This alternative surgery can be used to treat PSF in children.